Novel materials in the environment: the case of nanotechnology - UK. Royal Commission on Environmental Pollution (London, 2008)
"The report was prompted by concerns about potential releases to the environment from industrial applications of metals and minerals that have not previously been widely used. As the majority of the evidence the Commission received was almost entirely focussed on manufactured nanomaterials, the Commission decided to focus on this sector, as an exemplar. The report examines issues related to innovation in the materials sector and the challenges and benefits arising from the introduction of novel materials (specifically nanomaterials). The report makes recommendations on how to deal with ignorance and uncertainty in this area, which could also be applied to other areas of fast-paced technological development. The consultation exercise on the subject for this latest study, held between October and December 2005, yielded a substantial number of helpful responses, and the Royal Commission were grateful to all who contributed. Having considered all the responses, the Royal Commission decided that the environmental effects of novel materials and applications would be the most appropriate topic for the study. It was well supported, and repressents an area where, with the exception of nanotechnology, little work has been carried out to date. (...)"